Newspaper competition and content diversity: a comparison of regional media markets in Sweden - Nord, Lars W. (Papeles de Europa, 2013)
This article discusses the relationship between the newspaper market structure in a region and the diversity of local news. It introduces some partial results on studies based on substantial media concentration within two very different regiona newspaper markets in the North and in the South of Sweden. The findings suggest that the relationship between newspaper competition and local news diversity is rather complicated. The study gives some support to the thought that ruinous competition sometimes could be as bad for news diversity as monopoly media.